Perkembangan Psikologi Agama pada Individu Lajang dan Menikah - Mochammad Yazid Niamullah; Muhammad Zulfikar; Sururin Sururin; Yokna Latif Ramadhan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Religious psychology is an important aspect in understanding human behavior, emotional stability, and spiritual development in everyday life. Differences in social roles and responsibilities between unmarried and married individuals can influence the way individuals understand and practice religious values. This study aims to determine the differences in the development of religious psychology between unmarried and married individuals, particularly in terms of religious consistency, spiritual motivation, and emotional maturity. This research used a qualitative approach with a descriptive-comparative design. The subjects consisted of eight respondents, including four unmarried individuals and four married individuals. Data were collected through semi-structured questionnaires distributed using Google Forms in May 2026. The data analysis technique employed the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results showed that married individuals tend to have more stable religiosity and emotional maturity due to family responsibilities and support from spouses in carrying out religious practices. Married respondents also demonstrated better emotional control and viewed religion as a guide in maintaining family harmony. Meanwhile, unmarried individuals tend to experience fluctuations in worship consistency caused by environmental influences, social media, lifestyle, and personal motivation. However, several unmarried respondents still demonstrated strong intrinsic religious awareness. This study concludes that marital status influences the development of religious psychology, especially in emotional maturity, spiritual responsibility, and consistency in religious practices. This research is expected to contribute to the development of religious psychology studies related to religiosity and social life.